Integrated Fuzzy Multi-Criteria Decision Making Application within An Environmental Evaluation Framework: A Case Study in Türkİye - Mehmet Ali Taş; Akcan Yetgin, Serap (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The selection process of eligible suppliers in supply chains entails numerous challenges under rapidly evolving conditions. Environmental considerations in public discourse, competitive market structures, and emerging technological capabilities influence the decision-making procedures. Rather than the conventional criteria of cost and service, different criteria have more recently been taken into consideration. In this study, presenting a Turkish case study, environmental management, environmental agility and environmental technology dimensions and the criteria related to these dimensions are defined. A fuzzy SWARA-BWM method was implemented in an integrated way to cope with the supplier selection problem. Different scenarios were created and benchmarked. The results of the study indicate that environmental agility is the prominent dimension, while the most significant criterion is delivery speed. The optimal supplier alternative among the four alternatives was identified as . This study was carried out to contribute to the examination and modeling of supply chain management issues.